Analysis of the use of industry 4.0 technologies as competitive advantage; Análisis del uso de las tecnologías de la industria 4.0como ventaja competitiva - Omar Alexánder León García; Damián Madinabeitia (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
Industry 4.0 was born amid a technological breakthrough and development which set information out to become a valuable element in strengthening competitive advantages and innovation processes to improve organizations productivity performance. For this, the scientific and business community is debating the negative and positive effects of these technologies and their relationship with business management, in the search for sustainable solutions for organizations. In this sense, the main purpose of this article is to identify the perceptions of SME managers in Colombia on the importance of implementing information technologies to promote competitive advantages that match the pace of industry 4.0. The research method used in the study was analysed by sampling using the questionnaire as a data collection tool. 75 managers provided complete and useful answers to this research. The collected data were analysed using different regression models were carried out; showing like principal results that a greater use of these technologies generates a positive impact on the competitive ad-vantage related to price/cost, quality, delivery reliability, product innovation and time to market. Statistical Package for the Social Sciences (SPSS) was used to the analysis.
Keywords: O14; M15; 330; Industry 4.0; technology; competitive advantage; business performance